Pengaruh Sistem Produksi Dan Peran Penyuluh Pertanian Terhadap Keberhasilan Usahatani Jamur Tiram Putih (Pleurotus ostreatus) - Amar Romidin Sumarga; Euis Dasipah; Karyana KS (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2022)
This study aims to find out the relationship between the Production System And Role of Agricultural Extensionists on the Success of White Oyster Mushroom Farming (Pleurotus Ostreatus). The analysis unit is farmers of White Oyster Mushroom Farming. The technique of determining respondents was carried out in a census of 60 units. Analysis techniques are used pearson correlation and path analysis. The results of the study obtained by the production system in the business activities of white oyster mushrooms inCugenangSubdistrict are characterized at the level of application of white oyster mushroom cultivation technology consisting of dimensions: from the process of providing raw materials; production process; harvesting and post-harvest handling; Distribution and warehousing obtained a rate of achievement of 78.87 % good criteria. The role of PPL is related to the business activities of white oyster mushrooms inCugenangSubdistrict which consists of dimensions: Advisors; Technicians; Liaison; Organizer; and innovators obtained a level of achievement of 77.01 % good criteria. The success of the white oyster mushroom farming business inCugenangSubdistrict consisting of dimensions: productivity; product quality; continuity ; and farming efficient . Obtained a level of achievement of 77.50 % good criteria. There is a strong relationship between the role of PPL and the production system in the white oyster mushroom farming business inCugenangSubdistrict, indicated by the correlation coefficient r = 0.93. The better the role of PPL, the better the production system. The production system and the role of PPL have a positive effect on the success of white oyster mushroom farming inCugenangSubdistrict. Production System contribution was obtained 81,23 % and contribution of PPL Role 12.60 %.